Archives, the Digital Turn, and Governance in Africa - (:unkn) unknown (My University, 2019)
Abstract: With the rise of information technology, an increasing proportion of public African archives are being digitized and made accessible on the internet. The same is being done to a certain extent with private archives too. As much as the new technologies are raising enthusiasm, they have prompted discussion among researchers and archivists, on subjects ranging from matters of intellectual property to sovereignty and governance. Digital archiving disrupts archival norms and practices, opening up a field of reflection relatively little explored by historians. This article therefore seeks to reflect on the digital turn of African archives as a subject for study in its own right, located at the crossroads of political and economic interests.
Keywords: African Research